1998
DOI: 10.1097/00003246-199802000-00040
|View full text |Cite
|
Sign up to set email alerts
|

Decomplexification in critical illness and injury: Relationship between heart rate variability, severity of illness, and outcome

Abstract: Our data support the hypothesis that measures of heart rate power spectra are inversely related and negatively correlated to severity of illness and outcome in critically ill and injured children. The phenomenon of decomplexification of physiologic dynamics may have important clinical implications in critical illness and injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
1
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(94 citation statements)
references
References 27 publications
2
87
1
4
Order By: Relevance
“…In pediatric and adult studies, the sustained reduction of HRV has been correlated with the severity of illness, outcome and mortality rate (26)(27)(28)(29). When assessing outcome in neonates, Vergales et al found that neonates who died had lower SDNN compared to survivors (10 ± 5.1 ms vs. 24.3 ± 9.5 ms, P < 0.001) (12).…”
Section: Neurodevelopmental Outcomementioning
confidence: 99%
“…In pediatric and adult studies, the sustained reduction of HRV has been correlated with the severity of illness, outcome and mortality rate (26)(27)(28)(29). When assessing outcome in neonates, Vergales et al found that neonates who died had lower SDNN compared to survivors (10 ± 5.1 ms vs. 24.3 ± 9.5 ms, P < 0.001) (12).…”
Section: Neurodevelopmental Outcomementioning
confidence: 99%
“…27 Several researchers have demonstrated that low or decreasing HRV in intensive care unit (ICU) patients reflects greater severity of illness and predicts subsequent deterioration and mortality. [28][29][30][31][32][33] HRV analysis measures may provide the emergency physician with a readily available, noninvasive tool to identify patients with early systemic compromise who are at greatest risk for deterioration.…”
mentioning
confidence: 99%
“…The Vanderbilt University group demonstrated that HR variability is a good predictor of mortality in trauma patients as early as 12 h after admission and throughout ICU stay. 34---36 Correlations have also been reported between HR variability and severity of illness and outcome in critically ill and injured children 37 and diverse populations of critical ill patients. 38 In the present study, mortality was found to be related to the alteration of three vital constants and to the duration of the alteration, allowing all three to be used in a prognostic index with an acceptable discrimination capacity.…”
Section: Most Frequent Diagnosesmentioning
confidence: 99%